Answer:
[tex]c=-2[/tex]
Step-by-step explanation:
We are given the function:
[tex]f(x) = -2c + cx - x^2[/tex]
And that:
[tex]\displaystyle f^{-1} (5) = -1[/tex]
And we want to determine the value of c.
Recall that by definition of inverse functions:
[tex]\displaystyle \text{If } f(a) = b, \text{ then } f^{-1}(b) = a[/tex]
So, since f⁻¹(5) = -1, then f(-1) = 5.
Substitute:
[tex]f(-1) = 5 = -2c + c(-1) - (-1)^2[/tex]
Simplify:
[tex]5 = -2c - c - (1)[/tex]
Combine like terms:
[tex]6 = -3c[/tex]
And divide. Hence:
[tex]c = -2[/tex]
In conclusion, the value of c is -2.